A Resource of Mapped Human Bacterial Artificial Chromosome Clones - Cheung, Vivian G.; Dalrymple, Heather L.; Narasimhan, Sandya; Watts, Jason; Schuler, Gregory; Raap, Anton K.; Morley, Michael; Bruzel, Alan (Genome Research, 1999)
To date, despite the increasing number of genomic tools, there is no repository of ordered human BAC clones that covers entire chromosomes. This project presents a resource of mapped large DNA fragments that span eight human chromosomes at ∼1-Mb resolution. These DNA fragments are bacterial artificial chromosome (BAC) clones anchored to sequence tagged site (STS) markers. This clone collection, which currently contains 759 mapped clones, is useful in a wide range of applications from microarray-based gene mapping to identification of chromosomal mutations. In addition to the clones themselves, we describe a database, GenMapDB (http://genomics.med.upenn.edu/genmapdb), that contains information about each clone in our collection.